The influence of low temperature of the heat carrier on the modeled and actual thermal power of a steel plate central heating radiator - Młodawski, Marcin; Małek, Marlena; Klasek, Kacper (Instal, 2024)
The article is a reference to the European standard EN 442:2014, which is used, among others, to assess and verify the constancy of performance of a construction product in the form of a room heating device. It presents the results of tests of a popular and widely used steel plate radiator type C22, supplied with water at a temperature of 75oC÷35oC.The article presents the differences between the power values obtained according to EN 442, and determined in real conditions – taking into account the logarithmic mean temperature difference, a wide range of water mass flow and low temperature of the heat carrier. The thermal characteristics performed according to the relevant standard present underestimated power values in relation to the real conditions in which the radiator was tested. As a result of experimental tests, obtained in the accredited AB143 laboratory, an increase in thermal power of approx. 20% was found in the conditions of actual use of the device, in relation to the model characteristics., The article suggested the need to use new calculation methods for low temperature of the heat carrier conditions, consisted with the temporary state of art. The name of the radiator manufacturer is not mentioned, focusing on the issue under consideration. The work is addressed to a wide range of recipients, i.e. users, installers, designers and manufacturers of such devices.